Pengaruh Promosi Kesehatan Menstrual Hygiene Terhadap Pengetahuan Dan Sikap Remaja Menstruasi Awal - Meriem Meisyaroh Syamson; Murtini Murtini (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction: Personal hygiene behavior during menstruation is a very important thing to do in ensuring the health of the organs of adolescent girls both physically and mentally. Aim: know the effect of menstrual hygiene health promotion on the knowledge and attitude of early menstrual adolescents. Method: Quantitative research uses Pre-Experiments with the design of one group Pretest-posttest design, with purposive sampling with the Wilcoxon Test. Results: The findings of the study showed the knowledge and attitudes of adolescent girls after being given health promotion increased and had a good impact on adolescents’ menstrual hygiene. Conclusions; That there is an effect of menstrual hygiene health promotion on the knowledge and attitude of early menstrual adolescents.